The gentle reaper - Subramani, Arundhati (Research and Humanities in Medical Education, 2020)
This poem aims to bring out the difference between the doctor and the Grim Reaper, who is a personification of death. Often visualized as a black cloaked skeleton, he holds an hourglass, waiting for the last grain of sand to fall so he can take the soul to his abode, the realm of the dead, with a skillful stroke of his sharp scythe. Here, the doctor is referred to as the Gentle Reaper and as the Reaper not Grim to bring out the contrast, for he saves the soul and brings it back to our living world.